The The Socialization of Yam Noodles Making Without Food Preservatives At The Health Pioneer In Nganjuk District - Sutrisno Adi Prayitno; Maria Agustini; Ully Wulandari (Kontribusia : Research Dissemination for Community Development, 2020)
The training and community service activities about the Unborax healthy food were carried out at Nganjuk District Training Center, which was attended by the pioneer of health. The objective of the program is to introduce the health pioneers of Nganjuk district about the importance of healthy food and dangers from the use of food additives such as borax and formaldehydewhich is often circulated freely, to motivate people be able to make their own food without using harmful food additives. The making of Unborax noodles introduced to the community with yam fortification is also used to motivate people to love the local food that is functional value. The method used is a social mentality approach and provides guidance and direct participatory practice of direct participative to the target of the health pioneer in Nganjuk that can be delivered to the community in each village. This training and counseling program is conducted by providing education that provides knowledge about local food, recommended food additives and prohibited by the government. Then continue to practice making wet noodles fortification from yam. Hopefully the community is more conscious with healthy food and local resources. In addition, it can also be processed in the form of other products ready to consume. The achievement gained after the training in making wet noodle without borax is all participants are able to understand the importance of healthy food without any preservatives prohibited. In addition, this training is able to awaken the community initiative to serve healthy food it self and sell it so that it can increase the income in the family. Key words: yam, wet noodles, fortification, healthy food, borax and formalin.